Chromosomal Variability among Allopatric Populations of Erythrinidae Fish Hoplias malabaricus: Mapping of Three Classes of Repetitive DNAs - Cioffi, M. B.; Martins, C. [UNESP]; Centofante, L.; Jacobina, U.; Bertollo, L. A. C. (Karger, 2009)
Karyotype and chromosomal characteristics from 3 allopatric populations of Hoplias malabaricus, cytogenetically the most studied Erythrinidae taxon, were investigated using different staining techniques (C-, Ag-, and CMA(3) banding) as well as fluorescent in situ hybridization (FISH) to detect 18S rDNA, 5S rDNA, and 5SHindIII satellite DNA sites. The isolation, cloning and characterization of an 18S rDNA probe from H. malabaricus genome were also performed for the first time in order to develop a more specific probe. The 3 populations, named PR, CR, and DR, showed identical karyotypes, with 2n = 42 chromosomes composed of 11 m pairs and 10 sm pairs, without heteromorphic sex chromosomes, which characterize the populations as belonging to karyomorph A. In all populations C-positive heterochromatin was situated in the centromeric/pericentromeric regions of the chromosomes, as well as in the telomeric region of several pairs. A conspicuous proximal heterochromatic block on the long arm of pair No. 16 was the only GC-rich segment in the karyotypes. 5SHindIII satellite DNA was always mapped in the centromeric region of several chromosomes. The 18S rDNA sites were situated on the telomeric or centromeric regions, whereas the 5S rDNA showed an interstitial or proximal location in some pairs. Several chromosomes bearing these repetitive DNA sequences were shared by the 3 populations, alongside with some exclusive chromosomal markers. In this sense, population CR was the most differentiated one, including a syntenic condition for the 18S and 5S rDNA probes, as confirmed by double FISH. Thus, despite their inclusion in the same major karyotypic group, the distinct populations cannot be considered an absolute evolutionary unit, as evidenced by their inner chromosomal differentiations. Copyright (C) 2009 S. Karger AG, Basel
Keywords: Fish; Karyotype evolution; 5S rDNA; 5SHindIII satellite DNA; 18S rDNA